(untitled) - Wang, Paul S. (Pacific Grove, CA, 1999)
Provides complete coverage of Java programming, from basic concepts and procedures to advanced topics. This is one of the first Java books that is written as a text, not just as a professional reference, making it much more logical and readable than most trade books. Designed for readers with prior programming experience, the book introduces OOP, graphical user interfaces, networking, multithreading, and event-driven programming. These concepts and techniques are applied to the development of interesting programs and Java applets, with the careful attention to practical implementation details that has marked Wang's popular books on C, C++, and UNIX. Concepts and techniques are illustrated with complete, ready-to-run examples.
Keywords: Object-oriented programming (Computer science),Java (Computer program language),Lập trình hướng đối tượng (Khoa học máy tính),World wide web,Java (Ngôn ngữ lập trình máy tính),Mạng diện rộng